Interactive augmented reality storybook for early childhood education - Kuek, Poh Seng (2020)
In this advance era of technology, the application of integrating Augmented Reality has become more commonly used in education compare to last decade. This project is carried in terms of study whether implementing AR technology in education will solve or improve the problem of current situation faced by almost every student in any ages which is feeling loss of engagement towards study, do not have reading habits since youth, did not found fun while study and also the interaction between teacher and student. This project is a development of a proposed mobile application which in the field of integration of Augmented Reality technology with the physical storybook. The target audience of this application are children in early childhood education from aged 2 to 7 to cultivate their reading habits since youth. The scope of this proposed application is aim to increase the motivation, engagement and interaction of the target audience in a better and interesting learning environment compare with an ordinary storybook. Intergrading Augmented Reality in an ordinary storybook creates an immersive experience toward children and raise their interest in the content of storybook. Parental supervision is required while using the application, which also benefits the interaction between parents and also their children. Questionnaire are constructed and analysed to seek user’s opinion on the proposed mobile application where the proposed application is needed by the community and also analysing the reading habits of children. Agile Model of methodology are applied as the approach in order to develop this proposed system is this project. There are five phases included in Agile Model which is planning, requirement analysis, design, implementation and evaluation performing different task which helps to develop the project. Development tools such as Shotcut, Vuforia SDK, Visual Studio 2017, Blender and Unity 3D is used to develop the proposed mobile application. The appropriate computer language for developing this application will be C#.